The Effect of Work Motivation, Work Discipline, and Work Experience on the Performance of Palm Oil Harvesters at the Silinda Plantation of PT. Cinta Raja - Yulius Threeple Son Sagala; Zulham (Jurnal Ragam Pengabdian, 2026)
A decline in employee performance within a company—particularly a palm oil plantation company—will lead to a drop in the company’s productivity, resulting in losses that the company wishes to avoid. The performance of palm oil harvesters has fallen short of the company’s expectations, leading to significant financial losses. This study was conducted at one of the oil palm plantation companies, PT. Cinta Raja, at the Silinda Plantation, Silinda Sub-district, Serdang Bedagai District, North Sumatra Province. The results of this study indicate that there is no influence on work motivation, work discipline, and work experience among harvesting employees. This was derived from the results of data calculations and field observations at the research site. However, work experience does influence employee performance.